Cardio‐adipose tissue cross‐talk: relationship between adiponectin, plasma pro brain natriuretic peptide and incident heart failure. (10th April 2014) - Lindberg, Søren; Jensen, Jan Skov; Bjerre, Mette; Pedersen, Sune H.; Frystyk, Jan; Flyvbjerg, Allan; Mogelvang, Rasmus
<x xml:space="preserve">Abstract</x> Aims There is increasing evidence of cross‐talk between the heart, body metabolism, and adipose tissue, but the precise mechanisms are poorly understood. Natriuretic peptides (NPs) have recently emerged as the prime candidate for a mediator. In patients with heart failure (HF), infusion of NPs increases adiponectin secretion, indicating that NPs may improve adipose tissue function and in this way function as a cardio‐protective agent in HF. Accordingly we investigated the interplay between plasma adiponectin, plasma proBNP, and development of HF. Methods and results We prospectively followed 5574 randomly selected men and women from the community without ischaemic heart disease or HF. Plasma adiponectin and proBNP were measured at study entry. Median follow‐up time was 8.5 years (interquartile range 8.0–9.1 years). During follow‐up 271 participants developed symptomatic HF. Plasma adiponectin and proBNP were strongly associated (P < 0.001). Participants with increasing adiponectin had increased risk of incident HF (P < 0.001). After adjustment for confounding risk factors (including age, gender, smoking status, body mass ratio, waist–hip ratio, glucose, glycated haemoglobin, systolic and diastolic blood pressure, lipid profile, high sensitivity C‐reactive protein, estimated glomerular filtration rate, and physical activity) by Cox regression analysis, adiponectin remained an independent predictor of HF: the hazard ratio (HR) per 1 standard deviation (SD) increase in adiponectin was 1.20 [95% confidence interval (CI) 1.06–1.30; P = 0.003]. However, the association vanished when plasma proBNP was included in the analysis, HR 1.08 (95% CI 0.95–1.23; P = 0.26). Conclusions In conclusion, plasma adiponectin and proBNP are strongly associated. Increasing plasma adiponectin is associated with increased risk of HF. However, concomitantly elevated proBNP levels appear to explain the positive association between adiponectin and risk of HF.